2020
DOI: 10.3390/jcm9061897
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/Valsartan Improves Autonomic Function and Cardiopulmonary Parameters in Patients with Heart Failure with Reduced Ejection Fraction

Abstract: Background: Heart rate recovery (HRR) is a marker of vagal tone, which is a powerful predictor of mortality in patients with cardiovascular disease. Sacubitril/valsartan (S/V) is a treatment for heart failure with reduced ejection fraction (HFrEF), which impressively impacts cardiovascular outcome. This study aims at evaluating the effects of S/V on HRR and its correlation with cardiopulmonary indexes in HFrEF patients. Methods: Patients with HFrEF admitted to outpatients’ services were screened out for study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…A relevant question is whether these improvements had to be ascribed to the exercise training alone or whether other components of the rehabilitation intervention also concurred to the observed benefits. Theoretically, according to literature data showing an improvement in functional capacity and cardiopulmonary parameters in patients with HF (Giallauria et al, 2020;Malfatto et al, 2020;Dos Santos et al, 2021), we cannot dismiss the possibility that the optimization of pharmacological treatment might also have played a role. However, we have to underscore that, in our study, changes in therapy concerned a very limited number of patients over a limited number of days.…”
Section: Discussionmentioning
confidence: 93%
“…A relevant question is whether these improvements had to be ascribed to the exercise training alone or whether other components of the rehabilitation intervention also concurred to the observed benefits. Theoretically, according to literature data showing an improvement in functional capacity and cardiopulmonary parameters in patients with HF (Giallauria et al, 2020;Malfatto et al, 2020;Dos Santos et al, 2021), we cannot dismiss the possibility that the optimization of pharmacological treatment might also have played a role. However, we have to underscore that, in our study, changes in therapy concerned a very limited number of patients over a limited number of days.…”
Section: Discussionmentioning
confidence: 93%
“…A study assessing the early effects of ARNI on exercise tolerance in patients with HFmHF found that ARNI improved exercise tolerance, peak VO₂, and ventilatory efficiency at 6.2 months of follow-up ( Vitale et al, 2019 ). Giallauria et al found that ARNI therapy improves autonomic function, functional capacity, and ventilation ( Giallauria et al, 2020 ). In clinical practice, ARNI can be considered a drug for HFmrEF patients, however, further studies are needed to better elucidate the underlying mechanisms of this functional improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of HR recovery could be an alternative solution. Defined as the difference between peak HR and HR obtained 1 min after exercise cessation ( 51 ), the HR recovery is however, dependent on post-exercise recovery modalities ( 52 , 53 ). In the present study, HR recovery was probably affected by the 3-min unloaded pedaling of post-exercise recovery.…”
Section: Discussionmentioning
confidence: 99%